2024
DOI: 10.7759/cureus.58019
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sodium-Glucose Cotransporter-2 (SGLT2) Inhibitors on Cardiovascular Outcomes and All-Cause Mortality in Patients With Acute Coronary Syndrome: A Systematic Review and Meta-Analysis

Tanya Sinha,
Faria Khilji,
FNU Laraib
et al.

Abstract: The aim of this systematic review and meta-analysis was to investigate the impact of early sodium-glucose cotransporter-2 (SGLT2) initiation on long-term cardiovascular outcomes and all-cause mortality among patients with acute coronary syndrome (ACS). For this study, we adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guideline. Two researchers independently performed a comprehensive literature search on PubMed, Embase, and the Cochrane Library, spanning from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although no significant differences were observed between the two groups regarding all-cause mortality and cardiovascular mortality, the risk was lower in patients receiving SGLT2i. A recent meta-analysis by Sinha et al [18] reported a significant reduction in the risk of MACE, all-cause mortality, cardiovascular mortality, and cardiovascular-related hospitalizations in patients treated with SGLT2i compared to those in the control group. However, that meta-analysis included studies involving general acute coronary syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant differences were observed between the two groups regarding all-cause mortality and cardiovascular mortality, the risk was lower in patients receiving SGLT2i. A recent meta-analysis by Sinha et al [18] reported a significant reduction in the risk of MACE, all-cause mortality, cardiovascular mortality, and cardiovascular-related hospitalizations in patients treated with SGLT2i compared to those in the control group. However, that meta-analysis included studies involving general acute coronary syndrome patients.…”
Section: Discussionmentioning
confidence: 99%